Overexpressed Pseudogene HLA-DPB2 Promotes Tumor Immune Infiltrates by Regulating HLA-DPB1 and Indicates a Better Prognosis in Breast Cancer - Lyu, Lijuan; Yao, Jia; Wang, Meng; Zheng, Yi; Xu, Peng; Wang, Shuqian; Zhang, Dai; Deng, Yujiao; Wu, Ying; Yang, Si; Lyu, Jun; Guan, Feng; et al. (Frontiers in Oncology, 2020)
Immune checkpoint inhibitors (ICIs) have been successfully used for treating melanoma and non-small cell lung cancer. However, many patients with breast cancer (BC) show low response to ICIs due to the paucity of infiltrating immune cells. Pseudogenes, as a particular kind of long-chain non-coding RNA, play vital roles in tumorigenesis, but their potential roles in tumor immunology remain unclear. In this study that used data from online databases, the novel pseudogene HLA-DPB2 and its parental gene HLA-DPB1 were overexpressed and correlated with better prognosis in BC. Mechanistically, our results revealed that HLA-DPB2 may serve as an endogenous RNA to increase HLA-DPB1 expression by competitively binding with has-miR-370-3p. Functionally, gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis indicated that the HLA-DPB2/HLA-DPB1 axis was strongly relevant to immune-related biological functions. Further analysis demonstrated that high expression levels of the HLA-DPB2 and HLA-DPB1 were significantly associated with high immune infiltration abundance of CD8+ T cells, CD4+ T cells, Tfh, Th1, and NK cells, and with high expression of majority biomarkers of monocytes, NK cell, T cell, CD8+ T cell, and Th1 in BC and its subtype, indicating that HLA-DPB2 can increase the abundance of tumor-infiltrating lymphocytes in the BC microenvironment. In addition, the HLA-DPB2 and HLA-DPB1 expression levels positively correlated with the expression levels of programmed cell death protein 1, programmed cell death ligand 1, and cytotoxic T-lymphocyte-associated antigen-4. Our findings suggest that pseudogene HLA-DPB2 can up-regulate HLA-DPB1 through sponging has-miR-370-3p, thus exerting its anti-tumor effect by recruiting tumor-infiltrating immune cells into the breast tumor microenvironment, and that targeting the HLA-DPB2/HLA-DPB1 axis with ICIs may optimize the current immunotherapy for BC.